OVERVIEW OF MITOXANTRONE-A POTENTIAL CANDIDATE FOR TREATMENT OF BREAST CANCER - S., PREETHI; KUMAR, HITESH; RAWAL, VISHAL B.; AJMEER, RAMKISHAN; JAIN, VIKAS (International Journal of Applied Pharmaceutics, 2022)
Anthraquinones are one of the popular classes of aromatic compounds which possess potential anticancer properties by suppressing the nucleic acid formation and proteins essential to the survival of cancerous cells. Mitoxantrone (MT) is an antibiotic and antineoplastic agent belonging to the anthracycline class of compounds which exhibit minimal incident of drug resistance. It is a synthetic anticancer drug, bound to enzyme topoisomerase IIα inhibitor, and intercalates DNA topoisomerase IIα, preventing re-ligations in DNA strands fragmentation and disruption of DNA repair. The expression of this enzyme was used tumor cells marker because of its key function in cell proliferation. The cleavable complex of topoisomerase IIα is hypothesized to damage the DNA and may enhance apoptosis in tumor cell proliferation. The susceptibility of cells to mitoxantrone is associated with cell topoisomerase II α protein and lowered resistance in breast cancer line cell lines to topoisomerase IIα inhibitors. MT is an ABC-transporter in breast cancer, also designated to be associated with “Breast cancer resistance protein” (BCRP) and it is also a cell cycle non-specific anti-cancer drug and P-glycoprotein substrate. Multiple drug resistance is one of the major drawbacks of this drug which can be avoided by reducing the efflux of the drug from cancer cells by formulating drug by using lipophilic carriers. This manuscript discusses about MT's source, chemistry, physicochemical properties, anti-cancer effects of mitoxantrone and possible pathways, Mitoxantrone targeting topoisomerase II inhibitor for cancer therapy and its mechanism, Various Nano formulation development strategy, toxicity profile, and a few patents related information.